Daisy-Head Mayzie - Seuss, Dr. Dr. (New York Random House, 2016)
Young Mayzie McGrew becomes a sensation when a daisy grows out of the top of her head, and everyone attempts to get rid of it.
Keywords: Daisies -- Juvenile fiction; Fame -- Juvenile fiction; Daisies -- Fiction; Fame -- Fiction; Humorous Stories; Stories in rhyme; Stories in rhyme